Distribution of Helicobacter pylori colonisation and associated gastric inflammatory changes: difference between patients with duodenal and gastric ulcers. Issue 8 (August 1993) - Louw, J A; Falck, V; van Rensburg, C; Zak, J; Adams, G; Marks, I N
Abstract : AIMS--To determine the gastric distribution of Helicobacter pylori in patients with duodenal and gastric ulcers; and to examine the mucosal inflammatory response. METHODS--Patients with newly diagnosed, uncomplicated duodenal and gastric ulcers were endoscoped and two biopsy specimens each taken from the antrum and the body. Specimens were evaluated blind by one pathologist to determine H pylori activity (scored 0-3) and inflammatory changes (according to the Sydney classification). RESULTS--Adequate biopsy material was obtained from 40 and 44 patients with gastric and duodenal ulcers, respectively. Although antral colonisation with H pylori was more common in the antrum of the latter, the organism was equally likely to be found in the body of both sets of patients; the density of colonisation was higher in those with gastric ulcers. Active gastritis and mucosal atrophy were more common in the body of those with gastric ulcers; intestinal metaplasia was also more common in the antrum of these patients. CONCLUSIONS--Gastritis in patients with duodenal ulcers is mainly antral, but the incidence of gastric body colonisation with H pylori seems to be the same in patients with either type of ulcer. There is, however, a significant difference in colonisation density. The cause and importance of this are not obvious and may be related to either host or organism factors.